Talking about sex and sexual behaviour of young people in Ireland - Nolan, Anne; Smyth, Emer (ESRI, 2020)
New research from a joint ESRI/HSE Health and Wellbeing research programme analyses how young people receive information on sex and relationships. Using data from the Growing up in Ireland ’98 Cohort at 13 and 17 years of age, the research also examines the role of this information in shaping sexual behaviours among Irish adolescents. The research finds that four in ten 17 year-olds have not spoken to their parents about sex and relationships.